Correlation of serum IGF-1, AGEs and their receptors with the risk of colorectal cancer in patients with type 2 diabetes mellitus - Chen, Zeng; Hong, Qiao (Frontiers in Oncology, 2023)
Background According to epidemiological evidence, people with type 2 diabetes mellitus have a higher risk of developing colorectal cancer. Objective To examine the relationship between colorectal cancer (CRC) and serum levels of IGF-1, IGF-1R, AGEs,RAGE and sRAGE in patients with type 2 diabetes. Methods By using RNA−Seq data of CRC patients from The Cancer Genome Atlas (TCGA) database, we divided the patients into normal group(58 patients)and tumor group(446 patients), and analyzed the expression and prognostic value analysis of IGF-1,IGF1R and RAGE. Cox regression and the Kaplan-Meier method were used to determine the predictive value of target gene on clinical outcomes in CRC patients. In order to further combine CRC with diabetes research,one hundred forty-eight patients hospitalized in the Second Hospital of Harbin Medical University from July 2021 to July 2022 were enrolled and divided into CA and control groups. There were 106 patients in the CA group, including 75 patients with CRC and 31 patients with CRC+T2DM; the control group comprised 42 patients with T2DM. Circulating levels of IGF-1, IGF-1R, AGEs, RAGE, and sRAGE in the serum of the patients were measured using Enzyme-Linked Immunosorbnent Assay (ELISA) kits, and other clinical parameters were also measured during hospitalization. Statistical methods used were χ² test, independent samples t-test and Pearson correlation analysis were. Finally, we controlled for confounding factors and used logistic multi-factor regression analysis. Results Bioinformatics analysis showed that IGF-1, IGF1R and RAGE were highly expressed in CRC patients, and the patients with high expression also showed significantly lower overall survival rate. Through Cox regression analysis, IGF-1 can be used as an independent influencing factor of CRC. In the ELISA experiment, serum AGE, RAGE, IGF-1, and IGF-1R levels were higher in the CRC and CRC+T2DM groups than in the T2DM group, but the serum sRAGE concentrations in these groups were lower than those in the T2DM group (P < 0.05). Serum AGE, RAGE, sRAGE, IGF1, and IGF1R levels were higher in the CRC+T2DM group than in the CRC group (P < 0.05). In CRC+T2DM patients, serum AGEs were correlated with age (p = 0.027), and the serum AGE levels in these groups were positively correlated with RAGE and IGF-1 levels (p < 0.001) and negatively correlated with sRAGE and IGF-1R levels (p < 0.001). After correcting for confounding factors based on logistic multiple regression analysis, the effects of age, serum IGF-1 and IGF-1R on the development of CRC in patients with T2DM were statistically significant (p<0.05). Conclusion Serum IGF-1 and IGF-1R levels independently influenced the development of CRC in patients with T2DM. Furthermore, IGF-1 and IGF-1R were correlated with AGEs in CRC patients who also had T2DM, suggesting that AGEs may influence the development of CRC in T2DM patients. These findings suggest that we may be able to lower the risk of CRC in the clinic by regulating AGEs through the regulation of blood glucose levels, which will affect IGF-1 and its receptors.